Magnetic Nanoparticles with On-Site Azide and Alkyne Functionalized Polymer Coating in a Single Step through a Solvothermal Process - Romualdo Mora-Cabello; David Fuentes-Ríos; Lidia Gago; Laura Cabeza; Ana Moscoso; Consolación Melguizo; José Prados; Francisco Sarabia; Juan Manuel López-Romero (Pharmaceutics)
Background/Objectives: Magnetic Fe3O4 nanoparticles (MNPs) are becoming more important every day. We prepared MNPs in a simple one-step reaction by following the solvothermal method, assisted by azide and alkyne functionalized polyethylene glycol (PEG400) polymers, as well as by PEG6000 and the polyol β-cyclodextrin (βCD), which played a crucial role as electrostatic stabilizers, providing polymeric/polyol coatings around the magnetic cores. Methods: The composition, morphology, and magnetic properties of the nanospheres were analyzed using Transmission Electron and Atomic Force Microscopies (TEM, AFM), Nuclear Magnetic Resonance (NMR), X-ray Diffraction Diffractometry (XRD), Fourier-Transform Infrared Spectroscopy (FT-IR), Matrix-Assisted Laser Desorption/Ionization (MALDI) and Vibrating Sample Magnetometry (VSM). Results: The obtained nanoparticles (@Fe3O4-PEGs and @Fe3O4-βCD) showed diameters between 90 and 250 nm, depending on the polymer used and the Fe3O4·6H2O precursor concentration, typically, 0.13 M at 200 °C and 24 h of reaction. MNPs exhibited superparamagnetism with high saturation mass magnetization at room temperature, reaching values of 59.9 emu/g (@Fe3O4-PEG6000), and no ferromagnetism. Likewise, they showed temperature elevation after applying an alternating magnetic field (AMF), obtaining Specific Absorption Rate (SAR) values of up to 51.87 ± 2.23 W/g for @Fe3O4-PEG6000. Additionally, the formed systems are susceptible to click chemistry, as was demonstrated in the case of the cannabidiol-propargyl derivative (CBD-Pro), which was synthesized and covalently attached to the azide functionalized surface of @Fe3O4-PEG400-N3. Prepared MNPs are highly dispersible in water, PBS, and citrate buffer, remaining in suspension for over 2 weeks, and non-toxic in the T84 human colon cancer cell line, Conclusions: indicating that they are ideal candidates for biomedical applications.